PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS PERSUASI SISWA KELAS VIII SMP NEGERI 1 BATUSANGKAR - Margaresy, Tiara; Tamsin, Andria Catri; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
ABSTRACT There were three purposes of this study. First, describing the kill of writing persuasive texts of eighth grade students of SMP N 1 Batusangkar before using the think talk write cooperative learning model. Second, describing the skill of writing persuasive texts of the eighth grade students of SMP N 1 Batusangkar after using the think talk write cooperative learning model. Third, analyzing the effect of using the thibk talk write cooperative learning model on the skill of writing persuasive texts of eighth grade students of SMP N 1 Batusangkar. Kata kunci: pengaruh, kooperatif, think talk write, teks persuasi